The Effect Of Performance Allowances On Employee Performance In The Public Works And Spatial Planning Office Asahan Regency - Eva Agustina; Muhammad Isa Indrawan (Yayasan Multidimensi Kreatif, 2024)
This research was a quantitative associative causal study aimed at analyzing the relationship pattern between variables and determining the effect of Performance Allowance on Employee Performance. The study was conducted at the Public Works and Spatial Planning Office of Asahan Regency, with a population of 120 employees. The sampling technique used was simple random sampling. The data was obtained from questionnaires distributed to respondents consisting of employees from various divisions. The results showed that Performance Allowance had a positive and significant effect on Employee Performance. This was evidenced by the t-value of 11.457, which was greater than the t-table value of 1.65543, and the significance value of 0.000, which was less than 0.05. The regression coefficient of 1.619 indicated that every 1-point increase in Performance Allowance would cause a 1.619-point increase in Employee Performance, assuming other variables remained constant. In addition, the coefficient of determination test showed an Adjusted R Square value of 0.477 or 47.70%, indicating that Performance Allowance had a relatively high effect on Employee Performance, with the remaining 52.30% influenced by other factors not examined in this study. Overall, the results of this study identified that increasing Performance Allowance could contribute to improving Employee Performance at the Public Works and Spatial Planning Office of Asahan Regency